Nutrient and energy balance, and amino acid digestibility in weaned piglets fed wheat bran and an exogenous enzyme combination - M.A. Trindade Neto; J.C. Dadalt; C. Gallardo (Animal, 2020)
The digestive system of the weaned piglets can be affected by the type of ingredients present in the diet, and a high fibre content in diets can limit the use of other nutrients and energy. The study was conducted to determine the effects of multicarbohydrase (MC) and phytase (Phy) supplementation on the nutritive value of wheat bran (WB) in weaned piglets. Multicarbohydrase preparation had 700 U α-galactosidase, 2200 U galactomannanase, 3000 U xylanase and 22 000 U β-glucanase per kilogram of diet, and Phy had 500 phytase units – FTU/kg of diet. Twenty-five weaned piglets (6.1 ± 0.63 kg) at 21 days old were fed five diets in a completely randomised experimental design with a 2 × 2 + 1 (0 and 200 mg/kg MC; 0 and 50 mg/kg Phy; and basal diet – BD) factorial arrangement used to determine treatment effects. An additional group of piglets was fed a corn-basal diet during apparent digestibility of nutrients, and fed a 5% casein-corn starch basal diet during apparent and standardised ileal digestibility (SID) of amino acid evaluations. Piglets were individually caged until 38 days old, when Ileal digesta was collected at slaughter. Test diets were made by mixing the basal diets and WB 7 : 3 (w/w), with or without MC, Phy or the combination. There was an interaction trend (P = 0.07) between MC and Phy in the balance of ash, digestible energy (DE) and metabolisable energy (ME). Effects of MC (P < 0.01) on DM, N retention, DE and ME, as well as an effect of Phy (P < 0.05) on ash, DE and ME and a trend in protein digestibility (P = 0.07) also was observed. The enzyme combination showed effect (P < 0.05) on SID of Lys, Pro and Ser; as a trend (P < 0.07) on His, Thr and Val. Isolated, MC also suggested improving (P < 0.07) on SID of His, Lys, Ala (P < 0.05), while Phy improved (P < 0.06) SID of Leu, Lys, Met (P < 0.01), Thr, Val, Ala (P < 0.01), Pro and Ser (P < 0.05). The MC carbohydrate complex was characterised as a viable alternative to increase the apparent nutrients digestibility and SID of amino acids when WB was used in the diet of young pigs and, when combined with Phy, suggested an additive effect on the apparent use of energy.